The Mediator Role Of Organizational Loyalty On The Relationship Between Transformational Leadership And The Dimensions Of Innovation In The Educational Sector: An Analytical Research Of The Views Of A Sample Of Academic Staffs In The Salahuddin University - Haseba Salim Hamad (QALAAI ZANIST JOURNAL, 2020)
This research aims to examine the effect of transformational leadership on dimensions of innovation in the educational sector, through the mediator role of organizational loyalty. The current research is one of the few studies aimed at filling the research gap by studying organizational loyalty as a mediator variable in the relationship between transformational leadership and innovation that applied in the higher education sector. SPSS program was used to analysis the collecting data. Besides, Path analysis (Amos program) was used to measure the direct and indirect effect of the independent variable (transformational leadership) the on the dependent variable (innovation) through the mediator variable (organizational loyalty). The research was conducted in the Salahuddin University faculties. The results of the study showed the validity of hypotheses. Accordingly, a number of conclusions were formulated. The most important of these was the positive effect of transformational leadership on all dimensions of innovation. With regard to the non-direct influence of transformational leadership on innovation through organizational loyalty, the results of the statistical analysis were showed that transformational leadership has an impact on innovation. The research was concluded with a number of recommendations.